Prevalence and Health Correlates of Work-Life Conflict among Blue- and White-Collar Workers from Different Economic Sectors - Hämmig, Oliver (Frontiers in Public Health, 2014)
The research on work-life conflict (WLC) is largely neglected in occupational medicine and public health and typically limited to white-collar workers and public servants. This study therefore aims to explore possible differences in the prevalence of WLC and its association with health outcomes between white- and blue-collar workers from different work environments in Switzerland. Cross-sectional survey data collected in 2007 in the service sector and in 2010 in the industrial sector were used for statistical analyses. A subsample of university graduates employed by large service companies (N=1,170) from the first survey’s population was taken and compared with a subsample of low or unskilled industrial and construction workers with no or only compulsory education (N=489) from the second survey’s population. The results show almost consistently, and particularly in women, a lower prevalence of time- and strain-based forms and both causal directions of WLC in blue-collar workers. However, associations between different WLC measures and general, physical and mental health outcomes were found to be equally strong or even stronger among blue-collar workers compared to white-collar workers. Low or unskilled industrial and construction workers are less frequently affected by higher degrees of WLC but are then at no lower risk of suffering poor self-rated health or severe backaches and sleep disorders than university graduates working in the service sector with comparable exposure to WLC. In conclusion it can be stated that WLC turned out to be much less prevalent but equally or even more detrimental to health in blue-collar workers, who therefore need to be considered in future studies.